The Composition and Primary Metabolic Potential of Microbial Communities Inhabiting the Surface Water in the Equatorial Eastern Indian Ocean - Changling Ding; Chao Wu; Congcong Guo; Jiang Gui; Yuqiu Wei; Jun Sun (Biology, 2021)
Currently, there is scant information about the biodiversity and functional diversity of microbes in the eastern Indian Ocean (EIO). Here, we used a combination of high-throughput sequencing of 16S rRNA genes and a metagenomic approach to investigate the microbial population structure and its metabolic function in the equatorial EIO. Our results show that Cyanobacterial Prochlorococcus made up the majority of the population. Interestingly, there were fewer contributions from clades SAR11 (Alphaproteobacteria) and SAR86 (Gammaproteobacteria) to microbial communities than contributions from Prochlorococcus. Based on functional gene analysis, functional genes rbcL, narB, and nasA were relatively abundant among the relevant genes. The abundance of Prochlorococcus implies its typically ecological adaptation in the local ecosystem. The microbial metabolic potential shows that in addition to the main carbon fixation pathway Calvin cycle, the rTCA cycle and the 3-HP/4-HB cycle have potential alternative carbon fixation contributions to local ecosystems. For the nitrogen cycle, the assimilatory nitrate and nitrite reduction pathway is potentially the crucial form of nitrogen utilization; unexpectedly, nitrogen fixation activity was relatively weak. This study extends our knowledge of the roles of microbes in energy and resource cycling in the EIO and provides a foundation for revealing profound biogeochemical processes driven by the microbial community in the ocean.